The first single-stranded DNA virus targeting Pectobacterium belongs to the family Microviridae and demonstrates a broad host range to Pectobacterium brasiliense soft rot pathogens - Julie Stenberg Pedersen; Alexander Byth Carstens; Magnus Rothgardt; Anouk Viry; Frank Hille; Charles M.A.P. Franz; Witold Kot; Artyom Egorov; Gemma Atkinson; Lars Hestbjerg Hansen (Archives of Virology, 2026)
Pectobacterium brasiliense ( Pbr ) is known to be one of the most virulent Pectobacterium species and is generally widely distributed across the globe, especially known for causing soft rot in potato-tubers and black leg in potato-plants. Currently no treatment mechanism exists, and many studies have focused on alternative treatment approaches such as biocontrol agents. Several studies have used phages targeting Pectobacterium species as effective biocontrol agents. This study is the first description of a single-stranded DNA phage belonging to the family Microviridae that targets Pectobacterium . The novel Pectobacterium phage Mimer is proposed to belong to a new genus within the subfamily Bullavirinae in the family Microviridae . Phage Mimer has a genome size of 5879 nt with twelve predicted gene products. Seven out of twelve gene products could be assigned with a function based on either amino acid sequence or structural similarity. Gene synteny and phylogenetic analyses suggest that phage Mimer is part of the subfamily Bullavirinae . Phage Mimer proved to infect a broad range of Pbr isolates but showed a poor adsorption rate as only 17% of phage particles adsorbed within 10 min on the isolation host. Growth kinetics showed phage Mimer to have a latent period of 65 min and an average burst size of approximately 79 virions per cell. Phage Mimer is the first ssDNA phage targeting Pectobacterium and could be a promising biocontrol agent with great therapeutic potential, based on both the small genome size and the well-known genome architecture of model phage phiX174.

Paths to a sustainable food sector: integrated design and LCA of future food supply chains: the case of pork production in Sweden - Ulf Gunnar Sonesson; Katarina Lorentzon; Annica Andersson; Ulla-Karin Barr; Jan Bertilsson; Elisabeth Borch; Carl Brunius; Margareta Emanuelsson; Leif Göransson; Stefan Gunnarsson; Lars Hamberg; Anna Hessle; et al. (The International Journal of Life Cycle Assessment, 2016)

fMRI memory assessment in healthy subjects: a new approach to view lateralization data at an individual level - Maria Strandberg; Christina Elfgren; Peter Mannfolk; Johan Olsrud; Lars Stenberg; Danielle van Westen; Elna-Marie Larsson; Ia Rorsman; Kristina Källén (Brain Imaging and Behavior, 2011)

Asymmetric indirect interactions mediated by a shared parasitoid: connecting species traits and local distribution patterns for two chrysomelid beetles - Peter A. Hambäck; Johan A. Stenberg; Lars Ericson (Oecologia, 2006)

Tall herb herbivory resistance reflects historic exposure to leaf beetles in a boreal archipelago age-gradient - Johan A. Stenberg; Johanna Witzell; Lars Ericson (Oecologia, 2006)

Influence of biochemical quality on C and N mineralisation from a broad variety of plant materials in soil - Lars S. Jensen; Tapio Salo; Fridrik Palmason; Tor Arvid Breland; Trond M. Henriksen; Bo Stenberg; Anders Pedersen; Christina Lundström; Martti Esala (Plant and Soil, 2005)

Complex segregation analysis of hypospadias - Louise Fredell; Lennart Iselius; Andy Collins; Einar Hansson; Staffan Holmner; Lars Lundquist; Göran Läckgren; Jörgen Pedersen; Arne Stenberg; Gunnar Westbacke; Agneta Nordenskjöld (Human Genetics, 2002)